The Impact of Forest Fires on Soil Properties in Lainea District, South Konawe Regency - Mariana Zainun; La Panga Mpalasi; Asramid Yasin; Alamsyah Flamin; Hafidah Nur; Wa Ode Nanang Trisna Dewi; Herlan Hidayat; Wa Ode Hastiani Fahidu; Yuldhan Fadillah Liambo (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
Forest and land fires are a form of disturbance that has the potential to significantly change the physical, chemical, and biological properties of the soil. This study aims to determine the impact of forest fires on soil properties in the burned area in Lainea District, South Konawe Regency, by comparing soil conditions in the ex-fire area and intact forests as a comparison. Soil sampling was carried out in each area of ±10 ha, with analysis of physical properties including texture, lintan density, pore space, moisture content, and permeability; Chemical properties include N, P, K, C-organic, Al, KTK, and pH; biological properties in the form of total soil microorganisms; and erosion estimation using the Universal Soil Loss Equation (USLE) method. The results showed that forest fires increased porosity, moisture content, and soil permeability, but decreased the density of sand and particle density. In chemical properties, the content of N, P, K, and KTK was observed to be higher in the area of the fire excerpt with a more neutral pH, although this increase is suspected to be temporary because it depends on the nutrient supply from the ash, while the C-organic content and organic matter that determine long-term fertility decreased. The total number of soil microorganisms observed decreased in the area of the fire ex. The erosion potential in fire-savage areas was also observed to be much higher than that of intact forests, although this difference may also be influenced by the different slope conditions between the two areas, so it cannot be attributed solely to the loss of vegetation due to fire. The study concludes that the impacts of fire on soil properties are diverse, with some chemical changes appearing beneficial in the short term but not reflecting structural improvements in soil fertility.